PLANNING THE WORK OF AVIATION UNITS USING PROJECT MANAGEMENT TOOLS - D. V. Bogomolov; M. E. Kharchenko (Научный вестник МГТУ ГА, 2017)
The article deals with the problematic issues of planning the work of aviation units and offers one of the possible variants of their solutions by means of project management tools implementation in aviation units.As a key concept in the theory of planning, the author proposes introducing the concept of a project as a complex, non-repeating one-time action, limited in time, budget, resources and in clear guidance throughout the process, followingthe customer requirements. In aviation engineering service work, this also includes such works as operational preparationstypes, routine maintenance, aviation technology improvements, military repair etc.The use of network models can also easily specify the sequence of some of the actions (events), to make process flow charts and organizational charts.The main advantage of linear graphs is their clarity and simplicity. Linear graphs make it possible to optimize the work on a variety of criteria, including the equability of labor force, machinery, building materials, etc. At the same time,the main drawback of linear graphs is that they are difficult to correct in case of non-compliance with the deadlines or a change in their arrangement. These drawbacks are eliminated by a different form of scheduling - network charts.The scheme of planning the work of units using project management tools is given. To carry out the scheme theauthor proposes to use modern tools of project management, which allow to structure the process of maintenance activities through its decomposition into phases, tasks and subtasks, then to identify critical path tasks, construct the chart of implementation. The process model as a project allows to make the prognostic analysis and to improve the process according to it, for what a number of modern software packages that automate the functions of planning and planned types of work schedule control.